Takotsubo cardiomyopathy: a rare complication of acute viral gastroenteritis. Issue 3 (3rd May 2020) - Ashfaq, Ammar; Ullah, Waqas; Khanal, Shristi; Zain, Muhammad Abdullah; Thalambedu, Nishanth; Inayat, Faisal; Atiq, Muhammad Umair
ABSTRACT: Takotsubo Cardiomyopathy (TCM) is characterized by a transient but reversible ventricular dysfunction in post-menopausal females following, but not always, a recent emotional or physical stress. Typically, chest pain is reported as a presenting symptom in the majority of patients. The severe diarrheal illness secondary to acute viral gastroenteritis is not commonly reported as the stressor event prior to TCM. We report a unique case of a middle-aged male presented with syncope shortly after loose bowel movements. He was diagnosed with TCM and was successfully managed with supportive care. The purpose of this case is to make clinicians aware of this rare association.